Honorific Culture at Delphi in the Hellenistic and Roman Periods - Grzesik, Dominika, (Brill Studies in Greek and Roman Epigraphy ;, 2021)
The goal of this inscription-based study is to shed new light on Hellenistic and Roman Delphi by placing inscribed honours at the front and centre of the investigation. This book provides, for the first time, a comprehensive and coherent discussion of the Delphic gift-giving system, its regional interactions, and its honorific network. It employs both conventional and new scientific methods, including an analysis of quantitative trends in the epigraphic records and a Social Network Analysis (SNA) approach. The volume also addresses a broad spectrum of epigraphic topics and discusses current research questions as well as future perspectives.